The Squash Bug, Anasa Tristis (Heteroptera: Coreidae): A Potential Greenhouse Pest of Beit Alpha Cucumber - Silvia I. Rondon; Daniel J. Cantliffe; James F. Price (EDIS, 2004)
The squash bug, Anasa tristis (DeGeer) (Heteroptera: Coreidae), is considered an important pest of cucurbits in open fields in the U.S. (Bonjour and Fargo, 1989; Cook and Neal, 1999). In the greenhouse, the squash bug can infest Beit alpha cucumber causing considerable damage (Rondon et al., 2003) (Fig. 2). This document is HS992, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: October 2004.